Quiescence modulates stem cell maintenance and regenerative capacity in the aging brain - Kalamakis, Georgios; Stiehl, Thomas; Kupke, Janina; Mallm, Jan-Philipp; Anders, Simon; Marciniak-Czochra, Anna; Martín-Villalba, Ana (Cell, 2019)
Summary - The function of somatic stem cells declines with age. Understanding the molecular underpinnings of this decline is key to counteract age-related disease. Here, we report a dramatic drop in the neural stem cells (NSCs) number in the aging murine brain. We find that this smaller stem cell reservoir is protected from full depletion by an increase in quiescence that makes old NSCs more resistant to regenerate the injured brain. Once activated, however, young and old NSCs show similar proliferation and differentiation capacity. Single-cell transcriptomics of NSCs indicate that aging changes NSCs minimally. In the aging brain, niche-derived inflammatory signals and the Wnt antagonist sFRP5 induce quiescence. Indeed, intervention to neutralize them increases activation of old NSCs during homeostasis and following injury. Our study identifies quiescence as a key feature of old NSCs imposed by the niche and uncovers ways to activate NSCs to repair the aging brain.
Gesehen am 25.04.2019